Fabrication of an Integrated, Flexible, Wireless Pressure Sensor Array for the Monitoring of Ventricular Pressure - Natiely Hernández-Sebastián; Daniela Diaz-Alonso; Bernardino Barrientos-García; Francisco Javier Renero-Carrillo; Wilfrido Calleja-Arriaga (Micromachines)
This work presents the design, fabrication, and rigorous validation of a flexible, wireless, capacitive pressure sensor for the full-range continuous monitoring of ventricular pressure. The proposed system consists of an implantable set and an external readout device; both modules were designed to form an RCL resonant circuit for passive, wireless pressure sensing and signal retrieving. Using surface micromachining and flexible electronics techniques, a two-variable capacitor array and a dual-layer planar coil were integrated into a flexible ergonomic substrate, avoiding hybrid-like connections in the implantable set. The proposed arrangement (capacitor array and dual-layer coil) allows us to optimize the operation pressure range and sensing distance. The use of polyimide as both the flexible substrate and the passivation material is a key feature, ensuring a biocompatible, implantable set that is mechanically flexible and can be folded to a compact size to achieve minimally invasive implantation. An external readout device has also been developed using a discrete printed circuit board (PCB) approach to support pressure measurements. The pressure responsivity of the sensor was validated to the laboratory level using a controlled pressure chamber. The results obtained show that the capacitance value of the sensor changed from 5.68 pF to 33.26 pF as the pressure varied from 0 to 300 mmHg. Correspondingly, the resonance frequency of the implantable set shifted from 12.75 MHz to 5.27 MHz. The sensitivity of the capacitive sensor was approximately 0.58 pF/mmHg and the typical response time was 220 ms. The wireless system performance was evaluated in both air and synthetic biological tissue using a Maxwell–Wien bridge circuit. The results showed a sensing distance longer than 3.5 cm, even under moderate misalignment conditions (up to 1.5 cm). The output voltage was successfully measured, ranging from 502.54 mV to 538.29 mV, throughout the full pressure range, with a measurement error of ±2.2 mV.